2007
DOI: 10.1007/s10739-007-9130-z
|View full text |Cite
|
Sign up to set email alerts
|

Overheated Rats, Race, and the Double Gland: Paul Kammerer, Endocrinology and the Problem of Somatic Induction

Abstract: In 1920, Eugen Steinach and Paul Kammerer reported experiments showing that exposure to high temperatures altered the structure of the gonad and produced hyper-sexuality in ''heat rats,'' presumably as a result of the increased production of sex hormones. Using SteinachÕs evidence that the gonad is a double gland with distinct sexual and generative functions, they used their findings to explain ''racial'' differences in the sexuality of indigenous tropical peoples and Europeans. The authors also reported that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The Austrian Lamarckian zoologist Paul Kammerer and the pioneer endocrinologist Eugen Steinach (1920) found that exposing male rats to high temperatures led to morphological and physiolog-ical changes in their offspring and grandoffspring. They suggested that the presence of hormone-secreting interstitial cells adjacent to germ cells in the gonads facilitated hormonal interactions between them, and they claimed that heat produced a change in hormone production in interstitial cells, thus affecting germline cells and carrying hereditary consequences (see Logan 2007 for a discussion of Kammerer and Steinach's work). Although the validity of this claim and its possible interpretation in terms of epigenetic inheritance is at present unclear, the possibility that there are hormonal effects on epigenetic variation is no longer considered heresy.…”
Section: Cases Included In the Tablementioning
confidence: 99%
“…The Austrian Lamarckian zoologist Paul Kammerer and the pioneer endocrinologist Eugen Steinach (1920) found that exposing male rats to high temperatures led to morphological and physiolog-ical changes in their offspring and grandoffspring. They suggested that the presence of hormone-secreting interstitial cells adjacent to germ cells in the gonads facilitated hormonal interactions between them, and they claimed that heat produced a change in hormone production in interstitial cells, thus affecting germline cells and carrying hereditary consequences (see Logan 2007 for a discussion of Kammerer and Steinach's work). Although the validity of this claim and its possible interpretation in terms of epigenetic inheritance is at present unclear, the possibility that there are hormonal effects on epigenetic variation is no longer considered heresy.…”
Section: Cases Included In the Tablementioning
confidence: 99%
“…Weismann then started suggesting that direct environmental effects on the germ-plasm were possible, but that functional changes of organs could not cause a corresponding change in the germ-plasm due to the germ being physically sequestered from not only somatic cytoplasm and idioplasm (nuclear contents), but also the germcell's cytoplasm [47,50]. Furthermore, he believed that the idioplasm of the germ-cell was a substance of extreme stability, as it could absorb nourishment and grow enormously without changing its complex molecular structure.…”
Section: Bendichmentioning
confidence: 99%
“…1 Chronological summary of the key events that led to the discovery and characterization of cirNAs and EVs from 428 BC (a) to date (b). The research topics include inheritance theories (represented by triangles), Pangenesis and graft hybridization studies (diamonds), the inheritance of acquired characteristics (chevron), genetic material and inheritance (squares), soma-to-germline information transfer (crosses), metabolic DNA (circles), EVs (half circles), cirDNA (stars), the bystander effect (rectangles), mobile protein complexes (arrow), and cancer progression and/or metastasis (plus) (direct or parallel induction) [50]. As mentioned in ''August Weismann: the argument against IAC through introducing the Weismann barrier'', Weismann believed that these environmental effects would, in any case, only influence germ-plasm growth rate or induce changes in an entire species, effectively refuting the idea that adaptive traits could be inherited by an individual.…”
Section: Demonstrating Somatic Induction In Defence Of Iacmentioning
confidence: 99%
See 1 more Smart Citation
“…As late as 1924, in lectures given in Baltimore, Johns Hopkins geneticist H. S. Jennings reviewed much of the empirical evidence supporting the inheritance of acquired characteristics. He focused on the research of the Austrian zoologist, Paul Kammerer (Gliboff, 2006;Logan, 2007). Noting how controversial the notion had become by that time, Jennings also reviewed the criticisms directed at Kammerer's work.…”
Section: Introductionmentioning
confidence: 99%